The THERAPEUTIC LINK AS AN EFFECTIVE TOOL FOR PSYCHOANALYTIC THERAPY - Costa, Jedaias da Costa e (2020)
Within the context of psychotherapy, it is very valid to emphasize the importance of the therapeutic alliance, considering that the development of the link between analyst and analyst can provide effective changes in therapy. The objective of this research is to show, through a bibliographical reference, how the bond manifests itself in psychotherapy in order to contribute to the changes and acquisition of analyzed insight, in this way, making psychotherapy an effective process. In addition, show how the effectiveness of the alliance between analyst and analyst interferes with the progress of this relationship and how this can contribute to the success or failure of therapy. We sought to explain the different types of link established during the therapeutic process, as well as to analyze the changes made through the therapeutic alliance in psychoanalytic based consultations, in order to address how a well-structured link can affect the therapy. Finally, we seek to clarify the link changes and how this structured is for Pichon-Rivière.